Effects of Mn2+ doping on the electronic, structural, and optical properties of Cs2ZrF6: An ab initio study. (March 2022) - Ghazanfar, Mahpara; Khan, Rashid; Azam, Sikander; Nasir, Muhammad Farooq
Abstract: In this study, based on first-principles calculations, we investigated the effects on the structural, electronic, and optical properties of substitutional doping of Mn 2+ at the Cs-site in the Cs2 ZrF6 supercell (2 × 2 × 1) at three different concentration levels (2.8 %, 5.6 %, and 8.3 % ). The generalized gradient approximation with the Hubbard parameter (GGA + U) was used for all calculations. Our results demonstrate that Cs2 ZrF6 has a direct bandgap of 7.3 eV and it is a non-magnetic insulator material. The defective states are located within the electronic bandgap of pristine Cs2 ZrF6 and the number of defective bands increases with the doping concentration level in pristine Cs2 ZrF6 . According to our calculations, spin-polarization is observed in all Mn 2+ doped Cs2 ZrF6 at different concentration levels. These intermediate bands are induced due to the major contribution of the d -orbital of the Mn atom and the minor contribution from the s -orbital of the Mn atom. The real and imaginary parts of the dielectric function, extinction coefficient, refractive index, reflectivity, electron energy loss spectrum, optical conductivity, and absorption coefficient were calculated as functions of the photon energy. The optical properties of Cs2 ZrF6 :Mn 2+ are significantly better, especially for the spin-up states, thereby indicating that Cs2 ZrF6 :Mn 2+ is a potential candidate for use in optoelectronic devices.